Peach Rust (Transchelia spp.) - Daniel Mancero-Castillo; Ali Sarkhosh; Courtney Ligon; Mercy A. Olmstead; Philip F. Harmon (EDIS)
Peach rust is a fungal disease commonly caused by Tranzchelia discolor (Fuckel) Tranzschel & Litvinov that attacks plants in the genus Prunus, including peach, nectarine, almond, plum, apricot, and cherry. In the Southeastern United State, the fungus is most common on peach orchards during summer and fall. The peach rust severity depends on the climatic conditions (temperature and rainfall), hosts (peach cultivars) and geographic location. Fungus rust is spread by airborne spores, which depend on moisture for infection. Where warm temperatures and high rainfalls usually result in severe peach rust infections. Florida’s summer rainfall provide favorable conditions for peach rust development. Despite, all currently available cultivars of peach in Florida are susceptible to the disease (Adaskaveg et al. 2012). Further studies of subtropical peach cultivars have shown differences for peach rust tolerance, measured by leaf retention, and rust incidence in the orchards (Alves et al. 2014; Citadin et al. 2010)